Hotspot Network Security System From Brute Force Attack Using Pfsense External Firewall (Case Study of Wifi-Ku.Net Hotspot) - Angga Syaputera; Riska Riska; Yessi Mardiana (Penerbit Jurnal Indonesia, 2023)
Many activities that are often carried out on the internet network that users without realizing threaten their privacy. From the several cybercrime attacks, one of them is the brute force method, where the brute force method is a method that aims to gain access rights to enter a system by force by trying all possible usernames and passwords that the attacker has prepared in a wordlist. The purpose of this study is to find out how to implement a hotspot network security system from brute force attacks using PFSense external firewall on a wifi-ku.net hotspot. The research method used is experimental research methods, namely testing a variable against other variables objectively, systematically and controlled by predicting the causes and consequences of the problems that the writer examine on the hotspot network security system from brute force attacks using PFsense external firewall. The results of the research that was carried out before applying Pfsense external firewall, it is found that the brute force successfully entered Mikrotik router, and after applying Pfsense external firewall attack with Brute Force method is no longer able to enter Mikrotik router because Pfsense's external firewall blocked attacks from brute force.